PML/RARα plays a role for basal activity and retinoid-induced repression of the tissue factor promoter in acute promyelocytic leukemia cells - Tenno, Taavo; Öberg, Fredrik; Mackman, Nigel; Nilsson, Kenneth; Siegbahn, Agneta (Thrombosis and Haemostasis, 2003)
Constitutive expression of tissue factor (TF) by acute promyelocytic leukemia (APL) cells may contribute to thrombotic complications. In this study we examined the transcriptional mechanisms of all-transretinoic acid (ATRA)-induced down-regulation of TF in the APL cell line NB4, by analysis of stable clones expressing the luciferase gene under the control of 5’ flanking regions of the TF gene. We show that the TF promoter is constitutively active in NB4 cells, and that ATRA induces rapid suppression of the promoter. Basal activity and ATRA-induced suppression of TF promoter is determined by the proximal -383 to +121 bp of the promoter. Electrophoretic mobility shift assays demonstrate the binding of Fos/Jun complexes to two TF promoter AP-1 sites in this region. Both complexes were suppressed by ATRA treatment. The ectopic expression of the APL-specific PML/RARα oncoprotein in U-937 cells results in induction of TF mRNA and promoter activity. Interestingly, this PML/RARα-mediated increase in TF promoter activity is sensitive to ATRA treatment. These data indicate that TF expression in APL cells is exacerbated by the presence of the PML/RARα fusion protein, and implicates the loss of Fos/Jun binding to the TF promoter in ATRA-induced suppression of TF.
Keywords: Tissue factor; acute promyelocytic leukemia; retinoic acid; PML/RARα; AP-1